P5-S6.31 Sexual healthcare among female sex workers working outside of the main entertainment district in Tijuana, Mexico. (10th July 2011) - Rusch, M; Gallardo, M; Lozada, R; Lindsay, R; Mercer, V J; Zuniga, M L; Patterson, T L; Strathdee, S A
Abstract : Background: Sex work is quasi-legal in Tijuana, with a zone of tolerance (Zona Roja, or Red Light district), and a registration card system whereby female sex workers (FSW) pay an annual cost to cover HIV and STI testing. As healthcare efforts are concentrated in the Zona Roja, we set out to assess the frequency of Pap testing among FSW working outside this zone. Methods: Proyecto Amantes de la Salud (Lovers of Health Project) conducted baseline surveys among 403 FSW working in bars outside of Tijuana's Zona Roja using time-location sampling. Surveys included demographics, sexual and substance use behaviour, sex work characteristics and sexual healthcare practices. Average number of annual Pap tests over the past 5 years was calculated using left censoring for the denominator based on: (1) years sexually active and (2) years in sex trade. Descriptive statistics and logistic regression were used to assess factors associated with Pap testing in the past year. Results: Participants ranged in age from 18 to 55 (Median: 28; IQR: 23–32); all were born in Mexico and 98% reported being registered as an FSW. Sex partners included regular, non-client (25%), regular clients (79%) and non-regular clients (99%). Overall, 85% of women reported a pap test in the past year; however, only 35% of sexually active women and 52% of FSW had an average of at least one Pap test per year over the past 5 years see Abstract P5-S6.31 table 1 . A small proportion (4%) indicated they had never had a Pap test. In multivariate models, having a Pap test in the past year was negatively associated with income >3500 pesos/month, more years in the sex trade and having regular clients. Marginal positive associations remained with older age, reporting condom use less than half the time with non-regular clients and having any children. Discussion: Prevalence of pap tests in the past year was higher than expected and may be attributed to recent efforts by the Tijuana Municipal Health Services to increase outreach to FSWs in these areas. However, since initiating sex work, only half reported the recommended yearly Pap testing which is concerning given the increased risk for HPV infection and cervical cancer among FSW. Sexual health education, including where access services, is needed to encourage regular cancer screening among this high risk population, especially among younger women and women who have been working in the sex trade for longer durations.